Assessment of Middle age Women's Knowledge towards Household Hazards in AL –Amara City - neamah, rasha; mohammed, fatin (Iraqi National Journal of Nursing Specialties, 2016)
Objective: The aim of the study is assessing middle age women's knowledge toward household hazards, In primary health care centers at AL-Amara City. Methodology: A descriptive and analytic design is accomplish on non probability (Purposive sample) consisting of 150 middle age women select from four primary health care centers at AL-Amara City (AL-Uroba Primary Health Care Center,AL Zahraa Primary Health Care Center ,AL Hasen AL-Askerry Primary Health Care Center ,and Ali AL-Ridha Primary Health Care Center.) These centers are choose randomly from 21 primary health care centers in the first sector. The study is conduct from (1st November, 2013 to1st August, 2014).The questionnaire is consist of two main parts, including: part 1 socio-demographic characteristics, and part 2 women's knowledge toward household hazards consisted of two sections (knowledge toward household cleaners, Disinfectants, and food poisoning). Assesses women's knowledge( Adequate or In adequate) The content validity of questionnaires are determined through 17 panels of experts from different fields. Reliability of the questionnaire are determine through an application of spilt-half and computation of Cronbach's Alpha Correlation coefficients (r=0.83). The analysis of data is performed through the application of descriptive statistic and inferential statistical. Results: The findings of the study indicate that (31.3 %) of the study sample are in the age group (40-44) years, (24.0%) are able to read and write, (43.3%) are housewives, (54.0%) are married, (79.3%) are urban residency, (75.3%) are living in nuclear families and (42.7%) are from a moderate level of socio-economic status, Concerning women's knowledge have adequate knowledge toward household hazards, Recommendations: The study recommends: Raising women's awareness toward household hazards and reinforce the healthy behaviors, distributing of brochures and pamphlets for families include guidance concerning home safety hazards, and looking further studies increasing sampling size and focusing on women in bearing age.